Supply Chain Management Strategy for the New Normal (The Peerian Journal, 2022)
The supply chain concept has become a concern due to global competition and increasing customer demand for value because the Companies try to improve their industrial performance in terms of cost, delays, adaptability, variety and traceability. Thus, the information must be available in real time across the supply chain and this can not be achieved without an integrated software system for supply chain management. Supply chain members have to collaborate, sharing information for improving customer’s satisfaction.